Surgical outcomes of elderly patients aged more than 80 years with distal radius fracture: comparison of external fixation and locking plate - Yu-Yi Huang; Tung-Yi Lin; Chien-Hao Chen; Ying-Chao Chou; Chun-Yi Su (BMC Musculoskeletal Disorders, 2020)
Abstract Background To compare the outcomes after surgical intervention, including external fixation (EF) with the optional addition of K-pins or open reduction and internal fixation (ORIF) with a volar locking plate (VLP), in patients with distal radius fracture aged > 80 years. Methods We reviewed 69 patients with a distal radius fracture aged > 80 years who treated under surgical intervention from 2011 to 2017 retrospectively. Their demographic data and complications were recorded. Preoperative, postoperative, and last follow-up plain films were analyzed. The functional outcomes of wrist range of motion were also evaluated. Results 41 patients were treated with EF with the optional addition of K-pins, while 28 patients were treated with ORIF with a VLP. The radiological parameters, including ulnar variance and radial inclination, at the last follow-up were significantly more acceptable in the VLP group (p = 0.01, p = 0.03, respectively). The forearm supination was significantly better in patients treated with VLP (p = 0.002). The overall incidence of complications was lower in the VLP group (p = 0.003). Conclusion VLP provides better radiological outcomes, wrist supination and lower complication rates than EF. Therefore, although EF is still widely used because of its acceptable results and easy application, we recommend VLP as a suitable treatment option for distal radius fracture in the geriatric population aged > 80 years.